Combined Radiation and Temperature Effects on Brillouin-Based Optical Fiber Sensors - Jérémy Perrot; Adriana Morana; Emmanuel Marin; Youcef Ouerdane; Aziz Boukenter; Johan Bertrand; Sylvain Girard (Photonics, 2023)
The combined effects of temperature (from −80 °C to +80 °C) and 100 kV X-ray exposure (up to 108 kGy(SiO2)) on the physical properties of Brillouin scattering and losses in three differently doped silica-based optical fibers, with varying dopant type and concentration (4 wt%(Ge), 10 wt%(Ge) and 1 wt%(F)), are experimentally studied in this work. The dependencies of Brillouin Frequency Shifts (BFS), Radiation-Induced Attenuation (RIA) levels, Brillouin gain attenuation, Brillouin frequency temperature (CT) and strain (Cε) sensitivity coefficients are studied under X-rays in a wide temperature range [−80 °C; +80 °C]. Brillouin sensing capabilities are investigated using a Brillouin Optical Time Domain Analyzer (BOTDA), and several properties are reported: (i) similar behavior of the Brillouin gain amplitude decrease with the increase in the RIA; (ii) the F-doped and heavily Ge-doped fibers do not exhibit a temperature dependence under radiation for their responses in Brillouin gain losses. Increasing Ge dopant concentration also reduces the irradiation temperature effect on RIA. In addition, Radiation-Induced Brillouin Frequency Shift (RI-BFS) manifests a slightly different behavior for lower temperatures than RIA, presenting an opportunity for a comprehensive understanding of RI-BFS origins. Related temperature and strain sensors are designed for harsh environments over an extended irradiation temperature range, which is useful for a wide range of applications.